EUropean (Legal) Culture Reconsidered (CPP RPS 14/2009) - Cern, Karolina M.; Juchacz, Piotr W. (Center for Public Policy Research Papers Series, 2009)
All in all, the starting point of any considerations should be the clearest part of the whole. So, let us begin with two pretty obvious statements. The first one is that from an empirical point of view there are different legal laws; this means that national legal systems differ from one another. We can talk of Swiss law, German law, Polish law, American law and the like; we can also discuss two different types of legal law: common law or statute law. There is no doubt they are all diverse. The second statement applies to a theoretical level (not just empirical): Each theorist announces principles he thinks applicable to any legal system, yet each is actually best understood as describing a national legal system – English in the case of Hart, American in the case of Dworkin, German in the case of Habermas.